2016
DOI: 10.1111/eip.12374
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of functioning in people suffering from first‐episode psychosis 1 year into entering early intervention service in Hong Kong

Abstract: Factors predictive of functioning levels at the three time points were different. Phase-specific intervention should be offered to enhance functional recovery of people with first-episode psychosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 39 publications
4
3
0
Order By: Relevance
“…These results are consistent with the service statistics of the EI clinic in KCH and some studies with similar sampling populations (Chong et al, ; Petrakis, Penno, Oxley, Bloom, & Castle, ; Strakowski, Keck, McElroy, Lonczak, & West, ); however, they differ from the statistics of EI studies in other localities, which reported a younger mean age and a greater proportion of male patients. The following factors contribute to these differences: (1) exclusion of substance–related psychotic disorders in the local EI service; (2) the eligible age range, which is up to 64 years in the local EI service and (3) the age of onset of schizophrenia, which is later in women (roughly middle age) (Abel, Drake, & Goldstein, ; Chong et al, ). Other clinical characteristics were similar to the extant literature (Cotton et al, ; Sim et al, , ; Strakowski et al, ).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These results are consistent with the service statistics of the EI clinic in KCH and some studies with similar sampling populations (Chong et al, ; Petrakis, Penno, Oxley, Bloom, & Castle, ; Strakowski, Keck, McElroy, Lonczak, & West, ); however, they differ from the statistics of EI studies in other localities, which reported a younger mean age and a greater proportion of male patients. The following factors contribute to these differences: (1) exclusion of substance–related psychotic disorders in the local EI service; (2) the eligible age range, which is up to 64 years in the local EI service and (3) the age of onset of schizophrenia, which is later in women (roughly middle age) (Abel, Drake, & Goldstein, ; Chong et al, ). Other clinical characteristics were similar to the extant literature (Cotton et al, ; Sim et al, , ; Strakowski et al, ).…”
Section: Discussionsupporting
confidence: 89%
“…The sample included 128 patients; the mean age was 34.2 years, and more patients were female (53.9%) than male. These results are nia, which is later in women (roughly middle age) (Abel, Drake, & Goldstein, 2010;Chong et al, 2016). Other clinical characteristics were similar to the extant literature (Cotton et al, 2012;Sim et al, 2004Sim et al, , 2006Strakowski et al, 1995).…”
Section: Discussionsupporting
confidence: 86%
“…Chong et al 71 reported that baseline insight predicted function at six but not 12-month follow up in first-episode psychosis.…”
Section: Insight and Outcomementioning
confidence: 99%
“…In recent years, there has been an expansion of the early intervention service to cover a wider age range. In 2011, the early intervention service in Hong Kong was extended to provide service to patient aged between 15 and 64 years (Chong et al, ). In 2016, the NHS England published guidelines on the implementation of the early intervention service suggesting expanding the service to patient aged between 14 and 65 years (NHS England, the National Collaborating Centre for Mental Health and the National Institute for Health and Care Excellence, ).…”
Section: Introductionmentioning
confidence: 99%